Educação inclusiva em cursos de licenciatura: um estudo sobre possibilidades e limitações da educação a distância (EaD) para formação de professores - Silva, Josiberti Flávio Aparecido Monteiro da [UNESP] (2006)
The new laws that govern nowadays the education system demand a teachers' urgent training, enabling them to work with students with special educational needs in common school classrooms. Considering the Education Department regulation on the disciplines offer by distance in the higher education, the present work has as objective analyze the role of a distance course about inclusive education for bachelor of education students of a public university. Moreover, it aims at to survey the efficiency of the inclusive contents offer by distance, as well as the course organization for the definition of its limits and possibilities. By means of partnership with a research and studies group about human resources and teacher training in special education, constituted by academic professors and postgraduate students, was created the program of a course about inclusive education to be applied to distance, via Internet. After the adaptation for material web developed by the group, it used a Learning Management System that enabled the rising of enough data for a detailed analysis of the questions of proposed research for this work. After studies, it concludes that the contents teaching about school inclusion can be made in courses in the Education Distance modality, however, the research demonstrates, among others results, that its efficiency in promote the learning about that school inclusion is directly associated to the inter-activity degree that the course provides, come in their participants and professors. This interaction can be improved, in Distance Education case via Internet, using the available resources nowadays by the Learning Management System, that were used of incipient form in this work, just with a view to test them, obtaining, however, enough qualitative results for the work conclusions.